3-D Kinematics Using Moving Cameras. Part 1: Development and Validation of the Mobile Data Acquisition System - Lafontaine, D.; Lamontagne, M. (Journal of Applied Biomechanics, 2003)
Many human activities, particularly sporting skills, occur over large distances. But technical limitations have forced biomechanists to conduct studies only on portions of such skills. In this paper we present the design and validation of a mobile data collection system composed of a camera cart that allows the tracking of athletes along a larger portion of their movements. A key feature of this system is that it requires only a small field of view to record and analyze joint motions. The validation of this method was conducted with three approaches. For all approaches, intermarker distances obtained from real measures were compared to those obtained from digitized video data. In all three experiments, the results proved to be within the accepted error range of 5%. The net differences between measured values and digitized values ranged from 0.8 to 3 mm, while the relative errors ranged from 0.2 to 6%. This first experimentation using a mobile camera array to collect and reconstruct biomechanical data has proven to be valid and worth pursuing for recording and analyzing ice hockey skating.